ANAPHYLACTIC REACTIONS IN ANAESTHESIA - Silva, Wallace Andrino; Macêdo Pinheiro, Aline (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2020)
Despite the safety of anesthetic procedures having increased in recent decades, anaphylaxis has been recognized as one of the most common causes of death in medical practice. The clinical manifestations present with a wide spectrum, ranging from mild hypersensitivity reactions to anaphylactic shock and death. Any substance used during anesthesia can trigger anaphylactic reaction, with neuromuscular blockers being the most frequent (50 to 70%), followed by latex (12-16.7%) and antibiotics (15%). In the intraoperative context, the diagnosis becomes more difficult and late. The rapid recognition or clinical suspicion of intraoperative anaphylaxis must be followed by appropriate conduct in order to interrupt contact with the causative agent and the perpetuation of the immune response.